Microscale analysis systems for the study of proteins and proteases - Sellens, Kathleen Ann (Kansas State University, 2018)
In research and industry, almost all chemical analysis methods involve the separation and detection of compounds. Typically, these separations are performed using traditional methods that require volumes in the 10 μL to 10 mL range of sample and in the 200 mL to 2 L range for solvents. These methods are not suitable for low-concentration, volume-limited samples frequently associated with biochemical studies. One way to overcome these limitations is to move the separation and detection to the microscale. The use of the microscale separation technologies enables the study of biological systems that have, until now, been out of reach due to their small volumes or low concentrations. The research presented in this dissertation will discuss two examples of this shift to microscale separation technologies which can solve some small volume sample challenges. These include the detection of protease activity in blood samples for use in cancer detection and the identification of immune system cascade proteins in the mosquito Anopheles gambiae. In Chapter 2 a microfluidic method and device is proposed to monitor protease activities for cancer detection. In this method nanobiosensors are used to measure enzyme activity in biological fluids. These nanobiosensors consist of iron-iron oxide magnetic nanoparticles that are attached to peptide substrates specific for proteases through a disulfide bond. The nanobiosensors are controlled using a neodymium magnet which is attached through a 3D printed adaptor to a rotating motor for mixing and a linear stage to move the nanoparticles between different sections of the device. The separation and detection sections of the device are explained in Chapter 3. Chapter 3 describes the fabrication and optimization of a simple device for microfluidic isoelectric focusing(IEF). IEF is a separation method in which analytes are separated based upon their isoelectric, i.e. neutral charge, points. A reducing agent can be added to the IEF buffer to detach the nanoparticle from the peptide substrate, releasing it for focusing. IEF is also a concentration as well as separation method that will allow the peptide substrates to be focused up to 10⁶ fold. It has a high peak capacity and produces reliable, reproducible separation patterns based on the isoelectric point of the peptide. To meet the detection limits required for cancer detection with proteases, scanning laser induced fluorescence is selected as the method of detection. This scanning system can monitor the separation over time to observe the parameters affecting the separation which cannot be done with typical point or imaging detection systems and allows better separation. This custom automatic detection system can distinguish focused samples of 500 fM from the background with minimal noise from the scanning system. In Chapter 4 the identification of serine protease and inhibitor binding complexes in A. gambiae hemolymph using magnetic bead immunoaffinity chromatography was attempted. These proteases play a key role in the insect innate immunity system and form irreversible complexes. These complexes can be purified from a complex hemolymph sample using an antibody to one of the complex members. To separate the complexes from the hemolymph, Serpin 2 antibodies were attached to protein A coated magnetic beads and then incubated with the hemolymph. Once the purified complexes and Serpin 2 were eluted, the purified proteases were identified on Orbitrap MS. In an attempt to simplify the isolation of the complexes, a magnetic bead mixing rotor column was developed to help reduce the volume of the elution to increase the concentration. This method, however, was not robust and did not improve the concentration.
Keywords: MIcrofluidics; Analytical chemistry; Immunoaffinity chromatography; Isoelectric focusing